2003
DOI: 10.1046/j.1526-100x.2003.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Differences in Prescribed Fire Regimes on Patchiness and Intensity of Fires in Subtropical Savannas of Everglades National Park, Florida

Abstract: We investigated effects of fire frequency, seasonal timing, and plant community on patchiness and intensity of prescribed fires in subtropical savannas in the Long Pine Key region of Everglades National Park, Florida (U.S.A.). We measured patchiness and intensity in different plant communities along elevation gradients in “fire blocks.” These blocks were prescribed burned at varying times during the lightning season and at different frequencies between 1995 and 2000. Fire frequency, seasonal timing, and plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 35 publications
2
92
0
Order By: Relevance
“…Allan 2001, Slocum et al 2003, Russell-Smith and Edwards 2006. Grasses, the dominant component of the combustible fuel in these savannas, progressively cure and collapse with the onset of the dry season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allan 2001, Slocum et al 2003, Russell-Smith and Edwards 2006. Grasses, the dominant component of the combustible fuel in these savannas, progressively cure and collapse with the onset of the dry season.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been undertaken to better understand fire patchiness, for a variety of ecological and associated land management purposes, in the USA (Turner et al 1994, Slocum et al 2003, southern Africa (Hudak et al 2004) , Spain (Román-Cuesta et al 2009 and Australia (Russell-Smith et al 1997, Allan 2001, Russell-Smith et al 2002b, RussellSmith and Edwards 2006. Russell-Smith and Edwards (2006) reported that EDS fires have 80% probability of being of low severity and would therefore be expected to have greater internal patchiness than LDS fires.…”
Section: Introductionmentioning
confidence: 99%
“…Wet prairies typically have hydroperiods of less than 12 months and are thus dry seasonally, tending to burn more than once a decade, and even every 1-2 years if adjacent to pine savannas (Platt, 1999;Schmitz et al, 2002;Slocum et al, 2003).…”
Section: Wet Prairiementioning
confidence: 99%
“…Vegetation at these four sampling locations is typical of wet prairies consisting of mainly sawgrass marsh (C. jamaicense) and willow thickets (Salix), with Sagittaria and Typha in more open areas (Slocum et al, 2003). Vegetation at RRP (#3) is dominated by bald cypress (Taxodium distichum), with other bottomland hardwood species (e.g., Acer, Fraxinus, Annona) forming the subcanopy, and Utricularia, Eleocharis, ferns, and Asteraceae present in the understory.…”
Section: Interior Wetland Transect (Samples 1-7)mentioning
confidence: 99%
“…For example, in pine savannahs, fallen needles make up the fine fuels which, when suspended on grass tussocks, burn well (500-800°C) because of their resins and ventilation (Slocum et al 2003). Temperature measurements taken at the ground surface in longleaf pine forest by Glitzenstein et al (1995) ranged from 274 to 452°C.…”
Section: Prescribed Firementioning
confidence: 99%